FACTORS THAT INFLUENCE MONEY / M2 MONEY IN INDONESIA (DATA PERIOD Q1.2001 - Q4.2015) - Teddy Ch Leasiwal; Muhamad Subhan (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2021)
This study aims to analyze the demand for money (broad money / M2) with a model that uses the condition of non-stationary data so that it can estimate the need for money in the economy. The period of data studied is from Q1.2001-Q4.2015. The analysis technique used is the Vector Error Correction Model (VECM) by conducting data stationarity tests, cointegration tests, lag feasibility tests, VECM Estimates, Granger Causality Test, and Impulse Response Function analysis to determine the effect ofshock from other variables. The results of this study indicate that: 1) GDP has a positive influence both in the short and long term on the money supply (M2); 2) Exchange rates or exchange rates also have a positive influence on M2; 3) Interest rates negatively affect M2;4) Inflation has a positive effect on M2. Keywords: Money supply (M2), GDP, exchange rate / exchange rate, interest rates and inflation